2017
DOI: 10.1523/eneuro.0293-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Back to Pupillometry: How Cortical Network State Fluctuations Tracked by Pupil Dynamics Could Explain Neural Signal Variability in Human Cognitive Neuroscience

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 75 publications
4
24
0
Order By: Relevance
“…In conclusion, we used steady-state fMRI to study the relation between pupil dynamics and brain networks. Our results advance a potential important link between changes in pupil and cortical state (Schwalm and Rosales Jubal, 2017). It would be interesting to study how the pupil-related network evolves during altered states of consciousness.…”
Section: Resultssupporting
confidence: 79%
“…In conclusion, we used steady-state fMRI to study the relation between pupil dynamics and brain networks. Our results advance a potential important link between changes in pupil and cortical state (Schwalm and Rosales Jubal, 2017). It would be interesting to study how the pupil-related network evolves during altered states of consciousness.…”
Section: Resultssupporting
confidence: 79%
“…a dynamic visual attention task) significantly increased integration with arousal, which may hint that these effects may be in part related to task-related activity. Taken together, our results support the view that pupil size is a marker of ongoing network states (Schwalm & Jubal, 2017), and point towards arousal as one mechanism affecting brain coordination between specific areas in tasks involving different cognitive states.…”
Section: Discussionsupporting
confidence: 86%
“…Electrophysiological studies have revealed that pupil constriction is associated to slow and synchronous cortical responses and inattentive behavior. Conversely, the cortical activation during task engagement or locomotion shows a persistent desynchronized neuronal activity associated to the dilatation of the pupil (Reimer et al, 2014, 2016; McGinley et al, 2015b; Schwalm and Jubal, 2017). Pupil size fluctuations and cortical state variations are modulated by the central noradrenergic and cholinergic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, monitoring pupil dynamics could be a reliable proxy of the changes in cortical states (Reimer et al, 2014, 2016; McGinley et al, 2015a,b). More specifically, the release of acetylcholine (Ach) from the basal forebrain and noradrenaline (NA) from LC have been shown to drive both the state of cortical connectivity and the pattern of the pupil size oscillations also in resting conditions (Reimer et al, 2016; Schwalm and Jubal, 2017). At the peripheral level, both Ach and NA are neurotransmitters of the ANS (parasympathetic and sympathetic systems, respectively) also controlling the pupil diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation